Growth of urbanization in Himachal Pra-desh : A statistical analysis - Sharma, Ridima; Tanwar, Sakshi; Rizvi, Safder (International Journal of Engineering and Technology, 2018)
Cities appear as a major role player in the economy of any area reflecting the global integration of its economy as they house majority of large business groups. Migratory population and urban growth are direct contributors in this economic expansion, particularly in the present-day phase of globalization which in under developed countries causes densification and instability of agriculture and other existing land use thus bringing in the need of a proper land resource management.Focused attention is needed to integrate infrastructure development in various cities and linkages should be established between the creation and management of assets through a system of reforms for long-term sustainability. Himachal Pradesh is a hill state with some most difficult terrains of the country making the preparation of complete cadastral record of land nearly impossible only 80% of land is under revenue records. Thus the amount of habitable land decreases further with around 50 % of the land under forest cover. The aim of the study is to analyze the growth of urbanisation in Himachal Pradesh along with the factors responsible. This growth pattern can later be used to formulate proper land use management and infrastructure development policies for equitable development of the area.